2020
DOI: 10.1183/13993003.03142-2020
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 on patients with asthma

Abstract: BackgroundAn association between the severity of COVID-19 and the presence of certain chronic conditions has been suggested. However, unlike influenza and other viruses, the disease burden in patients with asthma has been less evident.ObjectiveTo understand the impact of COVID-19 in patients with asthma.MethodsUsing big data analytics and artificial intelligence through the SAVANA Manager® clinical platform, we analysed clinical data from patients with asthma from January 1st to May 10th, 2020.ResultsOut of 71… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
169
0
17

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(193 citation statements)
references
References 37 publications
7
169
0
17
Order By: Relevance
“…This is exactly the approach taken by Choi et al and Izquierdo et al in the two real-life studies in this issue of the European Respiratory Journal [ 16 , 17 ]. While Choi et al included all COVID-19 cases in Korea (n=7590) by using a national claims database, Izquierdo et al .…”
Section: Textmentioning
confidence: 70%
“…This is exactly the approach taken by Choi et al and Izquierdo et al in the two real-life studies in this issue of the European Respiratory Journal [ 16 , 17 ]. While Choi et al included all COVID-19 cases in Korea (n=7590) by using a national claims database, Izquierdo et al .…”
Section: Textmentioning
confidence: 70%
“…Our study is amongst the largest of 6 published reports on patients with severe asthma treated with biologics and shows the worst outcome of COVID-19. The other studies in asthma patients on biologic treatment reported cases of COVID-19, but out of a total of 19 confirmed COVID-19 patients admitted to the hospital, only 2 were intubated, and 2 died [ 15 , [18] , [19] , [20] , [21] , [22] ]. Compared to these other studies, the COVID-19 cases in our study were clearly more severe.…”
Section: Discussionmentioning
confidence: 99%
“…Since the outbreak there has been much debate about the extent to which asthma is a risk factor for susceptibility to SARS-CoV-2 infection or severe disease progression of COVID-19, and results of studies addressing these issues vary substantially [ [6] , [7] , [8] , [9] , [10] , [11] , [12] ]. Recent large studies and meta-analyses however suggest that asthma patients in general may not be at risk for severe COVID-19, which may be due to a potential protective effect of type 2 inflammation [ [13] , [14] , [15] , [16] , [17] ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dabei werden häufig gestellte Fragen anhand von 13 exemplarischen Fallbeispielen beantwortet. [31], Belgien [32], Frankreich [33], Brasilien [34], Russland [35], Japan [36] und den USA [37 -42] [112 -114]. Aufgrund der geringen Anzahl an publizierten Fällen ist eine sichere Beurteilung allerdings nicht möglich, zudem müssen immer auch die Komorbiditäten der Patienten beachtet werden [115].…”
Section: Epidemiologie Schwerer Verläufeunclassified